PENERAPAN MODEL PROJECT BASED LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATERI TEKS PROSEDUR MEMBUAT MOBIL MAINAN DI KELAS V SDN 1 PAGAR AIR KABUPATEN ACEH BESAR - Lasmi, Helpika; Safiah, Intan; Hasniyati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low level of student learning activities and learning outcomes in procedural text material in Grade V at SD Negeri 1 Pagar Air. Students’ scores were still below the Minimum Mastery Criteria (KKTP), and their participation in the learning process was relatively low. This study aimed to determine the improvement of students’ learning activities and learning outcomes through the implementation of the Project Based Learning (PjBL) model on procedural text material in making toy cars. This research employed a qualitative approach with a descriptive design. The subjects of the study were 22 fifth-grade students. Data were collected through observation, performance assessment using student worksheets (LKPD), learning outcome tests, and documentation. The data were analyzed through data reduction, data display, and conclusion drawing. The results showed that the implementation of the PjBL model increased students’ learning activities in discussions, group collaboration, and project implementation. In addition, students’ learning outcomes improved, as indicated by the majority of students achieving mastery according to the KKTP. Therefore, the Project Based Learning model is effective in improving learning activities and learning outcomes in procedural text material at the elementary school level.